The Effect of Marketing Mix on Student Decision to Choose a Private University - Bonar Bangun Jeppri Napitupulu; Dwi Ferdiyatmoko Cahya Kumoro; Masduki Asbari; Multi Nadeak (AGUSPATI RESEARCH INSTITUTA, 2023)
The purpose of this study was to examine and analyze the influence of the marketing mix elements which include product, price, place, promotion, people, process, and physical evidence on students' decisions to choose one of the private university campuses in Tangerang. This research uses primary data through a survey of 245 active students at the university concerned with the even semester of the 2022/2023 academic year. The collected data were processed and analyzed using SmartPLS software. The results of this study indicate that the seven factors of the marketing mix (marketing mix) have a positive and significant effect on the student's decision to choose to study at their current campus. An in-depth analysis of the managerial and social implications of the results of this study is discussed further in the body of this article.